PENYELESAIAN SENGKETA EKSPOR BIJIH NIKEL INDONESIA DENGAN UNI EROPA DALAM HUKUM PERDAGANGAN INTERNASIONAL - Hasudungan, Salomo Ebeneizer; Mangisi Simanjuntak; Edward ML Panjaitan (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2022)
The position of developing countries in international trade law is often portrayed unfavorably. Many articles criticize the imbalance in international trade rules, claiming that they mostly benefit developed countries. Generally, the concepts and regulatory drafts in international trade law are created by legal experts from developed nations and then offered to developing countries. As a result, these countries often fail to fully understand the long-term implications of the agreements they enter. Years later, they realize that the agreements tend to promote trade liberalization that disproportionately benefits the developed world, making trade disputes between countries inevitable. Most international trade disputes arise from national policies concerning tariffs, quotas, or subsidies. A notable example is the dispute between Indonesia and the European Union regarding the Indonesian government’s ban on nickel ore exports. In this case, Indonesia sought to prioritize its national interests, particularly in promoting downstream industries and preserving its natural resources. However, the EU challenged this policy at the World Trade Organization (WTO) under dispute case number DS592. This case highlights the ongoing struggle of developing countries to assert their sovereignty and economic priorities within a global trade system that often favors more developed economies.